Management of a xeroderma pigmentosum case with oral findings in a dental setup. (18th December 2012) - Banda, Vanaja Reddy; Banda, Naveen Reddy; Reddy, Ramesh; Banda, Praveen
Abstract : Xeroderma pigmentosum (XP) is heterogeneous group of disorder transmitted as autosomal recessive trait. It is characterised by photosensitivity, freckled pigmentation and premature skin ageing and malignant tumour development. The manifestations are due to a cellular hypersensitivity to ultraviolet light resulting from a defect in DNA repair. Multiple cutaneous neoplasms develop at a young age in persons with XP. Two important causes of mortality are metastatic malignant melanoma and squamous cell carcinoma (SCC). We report a case of XP in a 22 year-old male patient who developed SCC of lower lip with in a short period of 1 month.